Optimalisasi Pelayanan Kepolisian dalam Menangani Tindak Pidana Kekerasan Terhadap Perempuan dan Anak - Juni Ahyar; Safrida Safrida (Asia-Pacific Journal of Public Policy, 2020)
Optimization of the service implementation for reports of violence against women and children by the Protection Unit for women and children in the Banda Aceh City Police has not been effective due to several motives. The main problem is that a large number of victims are reluctant to report to the police. The reason is that a lot of acts of violence that occur among families are expected to be resolved among families without interventing by the police. The police always appeal to the whole communities if the incident has been repeated, it is hoped that they should immediately report to the police and the time needed to handle or complete cases of violence against women and children is two weeks. The case will be completed if the examination of the perpetrators, victims, and witnesses are not hampered, and as soon as a month, a completed file will be transferred to the prosecutor. Another problem encountered by the police is the unavailability of appropriate room for investigating violence against women and children. It is highly influential in the investigation process to arrest the perpetrators. Besides, the limited budget allocated for this unit also becomes a problem. Lacking public awareness regarding the handling of victims of criminal acts of domestic violence also becomes another problem.